STUDIES ON DEVELOPMENT AND STORAGE QUALITY EVALUATION OF BETALAINS RICH DRINK PREPARED FROM WILD PRICKLY PEAR (OPUNTIA DILLENII HAW.) FRUITS - N. S. THAKUR; MONIKA CHAUHAN; BHIMANYU THAKUR (The Bioscan, 2020)
The present study was undertaken for the development of RTS from wild prickly pear fruit and its quality evaluation during storage for six months. Different combinations of juice (10, 12, 14 and 16%), sugar syrup (12 and 15 oB) and 0.30 per cent acidity were tried to standardize proper combination for RTS. The RTS prepared with 14 per cent juice, 12 oB TSS and 0.30 per cent acidity was packed in glass and PET (Polyethylene terephthalate) bottles and stored for six months under ambient and refrigerated temperature conditions. RTS could be safely stored for a period of six months under both the storage conditions without much change in various quality characteristics. Various physico-chemical characteristics increased/decreased like TSS (12.00 to 12.48 oB), reducing sugars (7.15 to 8.74%), titratable acidity (0.30 to 0.26%), ascorbic acid (2.48 to 0.76 mg/100 g), betacyanins (9.50 to 9.36 mg/100 ml), betaxanthins (2.06 to 0.53 mg/100 ml) and total phenols (11.22 to 3.89 mg/100 g). However, changes were slower in refrigerated storage conditions as compared to that under ambient conditions. Both the packaging materials viz. PET and glass bottles were found suitable, with comparatively less changes occurring in glass bottles stored under refrigerated conditions.